Quantitative proteomics identified a novel invasion biomarker associated with EMT in pituitary adenomas - Zhang, Yu; Li, Lei; Ma, Xin; Liu, Chenan; Liu, Gemingtian; Bie, Zhixu; Yang, Zhijun; Liu, Pinan (Frontiers in Endocrinology, 2023)
Background: Complete resection of invasive pituitary adenoma is usually difficult, resulting in a high recurrence rate. Therefore, it is needed to find potential diagnostic markers and therapeutic targets for invasive pituitary adenoma. Methods: We collected samples from patients with invasive and non-invasive pituitary adenomas from Beijing Tiantan Hospital for protein extraction and quantitative analysis. We identified differential proteins (DEPs) by differential analysis of the two groups. The intersection of differential proteins related to invasion and epithelial-mesenchymal transition (EMT) in the GeneCards database was identified as EMT-DEPs. The protein network of EMT-DEPs was analyzed using the STRING database and Cytoscape software, and the hub EMT-DEPs were obtained by the MCC algorithm of the cytoHubba plugin. Correlation analysis was used to obtain the interpairing proteins among EMT-DEPs, and core EMT-DEPs were identified based on the number of paired proteins. The Venn program was used to identify the intersection of hub EMT-DEPs and core EMT-DEPs as key EMT-DEPs. Finally, a series of analyses plus experiments were used to verify the correlation of the target protein with invasion and EMT in pituitary adenoma. Results: Quantitative comparison of proteins between invasive and non-invasive pituitary adenomas indicated 833 differential proteins. The overlaps of EMT-related proteins and differential proteins consisted of 46 EMT-DEPs. There were 6 intersections between the hub EMT-DEPs and core EMT-DEPs. Using quantitative protein data and GSE169498 chip, we found that solute carrier family 2 member 1 (SLC2A1) was our target protein. SLC2A1 was significantly correlated with the invasiveness of pituitary adenoma, and the ROC curve was satisfactory. The functions and pathways of SLC2A1 and paired protein enrichment were closely linked to the EMT. Consistently, SLC2A1 expression was significantly and positively correlated with the expression of classical markers of EMT. The final experiment revealed that SLC2A1 was significantly upregulated in invasive pituitary adenoma. Conclusion: SLC2A1 is significantly upregulated in invasive pituitary adenoma with satisfactory predictive value. It may regulate EMT. It may be a potential diagnostic marker for invasive pituitary adenoma.